Oxpentifylline treatment of venous ulcers of the leg. - Colgan, M P (1990)
OBJECTIVE--To determine the effect of oxpentifylline on the healing of venous ulcers of the leg. DESIGN--Double blind, randomised, prospective, placebo controlled, parallel group study. SETTING--Four outpatient clinics treating leg ulcers in England and the Republic of Ireland. PATIENTS--80 Consecutive patients with clinical evidence of venous ulceration of the leg in whom appreciable arterial disease was excluded by the ratio of ankle to brachial systolic pressure being greater than 0.8. INTERVENTIONS--All patients received either oxpentifylline 400 mg three times a day by mouth or a matching placebo for six months (or until their reference ulcer healed if this occurred sooner) in addition to a locally standardised method of compression bandaging. MAIN OUTCOME MEASURES--The primary end point was complete healing of the reference ulcer within six months. The secondary end point was the change in the area of the ulcer over the six month observation period. RESULTS--Complete healing of the reference ulcer occurred in 23 of the 38 patients treated with oxpentifylline and in 12 of the 42 patients treated with a placebo. Life table analysis showed that the proportion of ulcers healed at six months was 64% in the group treated with oxpentifylline compared with 34% in the group treated with a placebo (log rank test chi 2 = 4.78, p = 0.03), which was significant (odds ratio = 1.81, 95% confidence interval 1.20 to 2.71). CONCLUSION--Oxpentifylline used in conjunction with compression bandaging improves the healing of venous ulcers of the leg.